Sustainable tourism marketing - Eduard Cristobal-Fransi; Natalia Daries; Berta Ferrer-Rosell; Estela Marine-Roig; Eva Martin-Fuentes (MDPI, 2020)
In this book, we introduce the themes and approaches covered in the issue Sustainable Tourism Marketing. Its objective was to analyze the main contributions made as a result of research related to sustainable tourism-marketing management and current trends in the field. This book gathered articles about the marketing of destinations, and the marketing and communication management of companies and tourism organizations from a sustainable tourism perspective.
Keywords: 330